The Determining Factors of Exchange Rate Fluctuations: A Case Study of Pakistan, Bangladesh, and India - Naqibullah, Haqbin; Najibullah, Mudasir; Rahim, Shahzad Mohammad; Ahmadullah, Hilali; Rahmatullah, Pashtoon (The journal of contemporary issues in business and government, 2021)
This constructive study identifies economic indicators that influence ER fluctuations in Bangladesh, India, and Pakistan from 1987 to 2018. The VECM model has been employed to identify the long-run causal movement from EXP, FDI, and FCE to RER. The Wald test is also applied as a VECM short-run representation to evaluate the model's short-run movement. This research's major determinations indicate that the long-term and short-term causal movements from FDI, EXP, and FCE to RER are momentous and significant. On top of that, the study's empirical recommend to policymakers and economy politicians that a shock to FCE, FDI, and EXP leads to fluctuations in RER. Moreover, FDI and EXP appreciate local currency against USD.